Resposta :
Resposta:
Solução:
[tex]\sf \displaystyle 3x^2- 12x + 3k = 0[/tex]
Coeficientes:
a = 3, b = -12 e c = 3k
Duas raízes reais e distintas:
[tex]\sf \displaystyle \Delta > 0[/tex]
[tex]\sf \displaystyle \Delta = b^2 -\:4ac[/tex]
[tex]\sf \displaystyle \Delta = (-12)^2 -\:4 \cdot 3 \cdot 3k[/tex]
[tex]\sf \displaystyle \Delta = 144 -\:36k[/tex]
[tex]\sf \displaystyle \Delta > 0[/tex]
[tex]\sf \displaystyle 144 - 36k >0[/tex]
[tex]\sf \displaystyle -36 k > - 144 \gets\text{\sf multiplicar por menos um. }[/tex]
[tex]\sf \displaystyle 36 k < 144[/tex]
[tex]\sf \displaystyle k < \dfrac{144}{36}[/tex]
[tex]\boxed{ \boxed { \boldsymbol{ \sf \displaystyle k < 4 }}} \quad \gets \text{\sf \textbf{Resposta } }[/tex]
[tex]\boldsymbol{ \sf \displaystyle S = \{x\in\mathbb{R}\mid k < 4 \} }[/tex]
Explicação passo-a-passo:
Lembrete:
Ao multiplicar por menos um inverte o sinal de desigualdade.